Intermediate Mutation Frequencies Favor Evolution of Multidrug Resistance in Escherichia coli - Denamur, Erick (Copyright © 2005 by the Genetics Society of America, 2005)
In studying the interplay between mutation frequencies and antibiotic resistance among Escherichia coli natural isolates, we observed that modest modifications of mutation frequency may significantly influence the evolution of antibiotic resistance. The strains having intermediate mutation frequencies have significantly more antibiotic resistances than strains having low and high mutation frequencies.